Factors influencing household debt in Malaysia / Nur Natasha Liyana Ramli - Ramli, Nur Natasha Liyana (Faculty of Business and Management, 2019)
This paper aim at finding out the factors influencing household debt in Malaysia which the household debt is monitor based on the total loans and financing from Commercials Banks and Islamic Banks. The variables are considered are gross domestic product (GDP), housing price (HP), interest rate (INT) and unemployment (UN). This study required 9 years data which is equal to 36 data by quarterly for each variable from 2010 until 2018. Methodology used for this study is using Multiple Linear Regression with series data. Thereafter, this test is to be conducted to observe the relationship of the independent variables with dependant variable which is household debt. Interactive software package E-view would be used for testing and analyzing the data collected. This study is attempting to investigate the relationship between the independent variables with the household debt and which variables contributes most to household debt. Findings from previous study mostly show that gross domestic product (GDP), housing price, interest rate and unemployment rate have a significant role in the determination of household debt As guidance to the past research that have been done, this study will examine the relationship between impact of independent variables and household debt.